Peningkatan Kemampuan Bahasa Inggris Bidang Hospitality Untuk Waiter dan Waitress di The Shalimar Boutique Hotel Malang - Isnaini Nur Safitri; Alvin Nouval; Eka Listianing Rahayu; Prima Beauty Kartikasari; Pritantina Yuni Lestari; Tri Astuti Handayani (Jurnal Pengabdian kepada Masyarakat, 2022)
This community service is intended to accommodate the needs of the hotel in improving English language skills in the hospitality sector for its employees, especially for waiters and waitresses, through English language training. The participants of this training were waiters and waitresses from The Shalimar Boutique Hotel, Malang. This activity is expected to be able to improve the quality of human resources at the Shalimar Hotel by enhancing the English skills of the waiters and waitresses, which will then be implemented to provide services and assist restaurant visitors and hotel guests from outside Indonesia. This activity was carried out in five stages, namely planning (to determine the number of participants who were involved and the materials needed in training), coordination with the hotel (to ensure that the plans made are in accordance with their needs), preparation of teaching materials/materials, implementation of training, and evaluation (providing questionnaires to training participants regarding the implementation and training materials).